Method for screening rice with high popping capacity - CGIAR Research Program on Rice (2019)
A method for the screening of rice germplasm for the production of fully gelatinized starch for infant formulas has been demonstrated. Two methods for the production of fully gelatinized carbohydrate sources from rice are being tested.